The Ravenmaster : my life with the ravens at the Tower of London - Skaife, Christopher, 1965- (Farrar, Straus and Giroux, 2018)
"A narrative by the Tower of London's official Ravenmaster about what it's like to live among the ravens at England's most famous national monument, woven together with insight from folklore, history, and contemporary behavioral science about this unusual bird"--